Flight directions of songbirds are unaffected by the topography of Lake Erie's southern coastline during fall migration. Issue 3 (17th August 2021) - Anderson, Ian A.; Gesicki, David V.; Bingman, Verner P.
Abstract: Migrating birds often encounter ecological barriers to fueling and other costs that can influence their flight directions. During spring migration, many migrants deviate westward along the southern coast of Lake Erie's western basin instead of continuing to fly the more northerly, broad‐front direction and crossing the lake. The goal of this study was to determine if migrants arriving at the same locations along the southern coast of Lake Erie in autumn, after having now already flown over the lake, would similarly respond to the coastal features despite the different decision making, adaptive profile. During the fall migrations of 2015–2017, flight directions of individual migrants, overwhelmingly passerines, were recorded by an infrared camera from three coastal sites along the southern coast of Lake Erie's western basin. The regional broad‐front direction of migration was taken from the WSR Doppler weather radar located near Cleveland, Ohio. Across multiple analyses, no differences in flight directions were observed either across the three observation sites or with respect to the broad‐front direction. Generally, migrants flew in a south‐southwesterly direction irrespective of location. Further, we found no differences in the flight directions of migrants early in the night compared to later in the night, suggesting that the energetic state did not substantially impact flight directions. In contrast to spring migration, the ecological boundary on Lake Erie's southern coast was not associated with any change in the flight directions of songbirds during fall migration, suggesting that migratory context is a critical factor determining how migrants may respond to environmental, topographic features. RESUMEN: Las direcciones del vuelo de aves cantoras no están afectadas por la topografía de la costa sur del Lago Erie durante la migración de otoño Las aves migratorias, con frecuencia encuentran barreras para el reabastecimiento de energía y otros costos que pueden influenciar las direcciones del vuelo. Durante la migración de primavera, muchos migrantes se desvían hacia el oeste a lo largo de la costa sur de la cuenca occidental del Lago Erie, en lugar de continuar volando hacia el norte directamente para cruzar el lago. El objetivo de este estudio fue determinar si los migrantes que llegan a las mismas localidades de la costa sur del lago Erie en otoño, después de haber volado por encima del lago, responden similarmente a las características de la costa, a pesar del perfil adaptativo en la toma de decisiones. Durante las migraciones de otoño de 2015–2017, registramos las direcciones de vuelo de migrantes individuales, principalmente paseriformes, utilizando las cámaras infrarrojas de tres localidades costeras a lo largo de la costa sur de la cuenca occidental del lago Erie. La dirección regional de frente amplio de la migración fue medida a través del radar climático Doppler WSR, ubicado cerca de Cleveland, Ohio. A través de múltiples análisis, no observamos diferencias en las direcciones del vuelo, ni utilizando los datos de los tres sitios de observación, ni la dirección de frente amplio. En general, los migrantes volaron con dirección sur‐suroeste independientemente de la ubicación. Adicionalmente, no encontramos diferencias en las direcciones de vuelo de migrantes desplazándose temprano o tarde en la noche, lo cual sugiere que el estatus energético no afecta sustancialmente las direcciones del vuelo. En contraste con la migración de primavera, los límites ecológicos en la costa sur del lago Erie no estuvieron asociados con ningún cambio en las direcciones del vuelo de las aves cantoras durante la migración de otoño, sugiriendo que el contexto migratorio es un factor crítico que determina como los migrantes responden a las características ambientales de la topografía.